Improving the Reliability of Bootstrap Tests - Russell Davidson; James G. MacKinnon (Queen's University, Department of Economics, 2000)
We first propose procedures for estimating the rejection probabilities for bootstrap tests in Monte Carlo experiments without actually computing a bootstrap test for each replication. These procedures are only about twice as expensive as estimating rejection probabilities for asymptotic tersts. We then propose procedures for computing modified bootstrap P values that will often be more accurate than ordinary ones. These procedures are closely related to the double bootstrap, but they are far less computationally demanding.
Keywords: C12; C15; 330; Double Bootstrap; Monte Carlo; Specification Test; Bootstrap P Value; Bootstrap Test